Marriage in the absence of wali nasab: procedural difficulties in obtaining consent from a wali raja - Abas, Afridah; Mohd, Azizah; Mohd Yusof, Naziri (University Putra Malaysia, 2015)
Marriage in Islam is a sacred institution. It is a form of ritual submission towards the Almighty God. In order to constitute a valid marriage, one of the pre-requisite is that the marriage must be in the presence of the female party’s blood relatives guardian (wali nasab) or at least his consent is obtained. In the absence of such guardian or his consent e.g. through a deputed power, the marriage shall render invalid unless the the marriage is taken over or solemnized by the head of State or his deputy (Wali Raja) i.e. the wali who has a general power over all Muslims. Nevertheless, there is contention that there are marriages that are in need of solemnization by a Wali Raja prolong most probably due to procedural difficulties that arise in the process of application for a Wali Raja and other factors. This paper seeks to examine whether this contention is true and what are the procedural difficulties in obtaining such consent of Wali Raja and accordingly ways to overcome those difficulties if any. The research is basically qualitative where analysis will be based on written procedures and practices outlined by the law. It is hoped that the research will be beneficial to all researchers, academicians, legal fraternity and the public as a whole.